Direct agreements and their role in project finance - Molina Rey de Castro, Fernando (2016)
The direct agreements perform an essential role in the viability of financing of projects. Its proper regulation determines its course, the prevention and management of possible consequences. Therefore, it is important to know this legal concept that has scarcely been studied in the doctrine. In this article, the author develops legal treatment of this legal concept, its definition, main terms and regulation in the Peruvian legal system.